2015
DOI: 10.1002/mas.21474
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry for the elucidation of the subtle molecular structure of biodegradable polymers and their degradation products

Abstract: Contemporary reports by Polish authors on the application of mass spectrometric methods for the elucidation of the subtle molecular structure of biodegradable polymers and their degradation products will be presented. Special emphasis will be given to natural aliphatic (co)polyesters (PHA) and their synthetic analogues, formed through anionic ring-opening polymerization (ROP) of b-substituted b-lactones. Moreover, the application of MS techniques for the evaluation of the structure of biodegradable polymers ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 89 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…The ESI-MS/MS spectrum of sodium adduct at m / z 911 also showed the fragment ion at m / z 811, grouped in a cluster containing three fragment ions, which may correspond to oligomers having the same degree of polymerization but having a different a content of HB and HV units. The fragmentation results allowed us to confirm that in the presence of O-PEW carbon source the PHA formed was composed of 3-hydroxybutyrate, 3-hydroxyvareate as well as 3-hydroxyhexanoate co-monomer units which are randomly distributed along the oligomer chain [34,38,40]. Moreover, with respect to the hitherto reported studies, this research demonstrated the possibility of PHA structure evaluation even when the content of HV and HH is lower than 5%, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESI-MS/MS spectrum of sodium adduct at m / z 911 also showed the fragment ion at m / z 811, grouped in a cluster containing three fragment ions, which may correspond to oligomers having the same degree of polymerization but having a different a content of HB and HV units. The fragmentation results allowed us to confirm that in the presence of O-PEW carbon source the PHA formed was composed of 3-hydroxybutyrate, 3-hydroxyvareate as well as 3-hydroxyhexanoate co-monomer units which are randomly distributed along the oligomer chain [34,38,40]. Moreover, with respect to the hitherto reported studies, this research demonstrated the possibility of PHA structure evaluation even when the content of HV and HH is lower than 5%, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Development of soft ionization techniques in mass spectrometry made the attempt to solve the difficult question regarding the molecular structure of copolymers more likely. Thus, structural studies of biodegradable copolymers with the use of multi-stage electrospray mass spectrometry (ESI-MS n ) were performed [38]. This mass spectrometry technique was applied to determine the co-monomer unit composition and composition distribution in bacterial PHA copolymers based on the analysis of their oligomers obtained by partial depolymerization (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of polymer degradation products having characteristic end groups was revealed and differentiated by the application of modern MS techniques [110]. The assessment of polymer degradation products having characteristic end groups was revealed and differentiated by the application of modern MS techniques [110].…”
Section: Factors Influencing the Biodegradability Of Polymersmentioning
confidence: 99%
“…The anionic ROP of β-substituted βlactones seems to be a perfect tool for the preparation of analogues of natural aliphatic biopolyesters, PHAs with the desired molecular structure, including the structure of the end groups [75]. Using this approach, with the aid of metalfree anionic initiators, block and random synthetic PHA copolymers can be prepared by anionic ROP of βbutyrolactone with comonomeric β-substituted β-lactones and characterized at the molecular level [76].…”
Section: Polymerization Techniques In Synthesis Of Functional (Bio)dementioning
confidence: 99%